2018
DOI: 10.1177/2333721418775551
|View full text |Cite
|
Sign up to set email alerts
|

Perceived and Functional Balance Control Is Negatively Affected by Diminished Touch and Vibration Sensitivity in Relatively Healthy Older Adults and Elderly

Abstract: Background: Severe diminished foot somatosensation, for example, caused by neuropathies and advanced aging, contributes to balance deficits and increased fall risk. However, little is known about somatosensory impairment and functional and subjective balance problems in relatively healthy elderly. Method: Vibration perception thresholds (VPTs) were assessed with a biothesiometer and tactile pressure sensation thresholds (TPSTs) with 20 monofilaments in 34 relatively healthy community-dwelling older adults (M =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Our findings demonstrate the proof-of-concept to use the mTUG subphases as a screening tool for deficits in clinically relevant sensory system performance, impacting on everyday mobility performances which are required for safe and independent ambulation [3]. The results are also in line with a recent study of Hafström et al [31], which demonstrated that an impaired somatosensory system impacts on postural stability and balance control.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings demonstrate the proof-of-concept to use the mTUG subphases as a screening tool for deficits in clinically relevant sensory system performance, impacting on everyday mobility performances which are required for safe and independent ambulation [3]. The results are also in line with a recent study of Hafström et al [31], which demonstrated that an impaired somatosensory system impacts on postural stability and balance control.…”
Section: Discussionsupporting
confidence: 87%
“…These factors also coincide with good quality of life ( 17 ). Since most stability issues originating from vestibular and other sensorimotor deficits can be addressed, or at least ameliorated, it is critical that they are detected by the health care system ( 46 , 50 ). The interventions to enhance and maintain postural control during aging should preferably be multimodal, able to detect and address co-morbidities, such as pain and mental strain, and performed in a structured but still adjustable, customized way ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, this is the first study that correlates TUG with VPT in T2DM patients. Two studies have also investigated the possible relationship between USVP and TUG in older people [43] and people with spinal canal stenosis [44]. However, no statistically significant correlations were found in any of them.…”
Section: Discussionmentioning
confidence: 99%